Unplanned pregnancy and awareness of emergency contraception: a postpartum period survey. (2nd November 2021) - Baser, Emre; Aydogan Kirmizi, Demet; Kasapoglu, Taner; Fırtına Tuncer, Serap; Ozturk Başarir, Zehra; Salgur, Funda; Bilge, Melek; Altinbas, Sadiman Kiykac; Tapisiz, Omer Lutfi
Abstract: Objectives: The study aimed to determine the awareness of emergency contraception (EC) and knowledge of its use as well as the unplanned pregnancy rate among women in the immediate postpartum period in Ankara, Turkey's second largest city. Methods: Interviews were carried out among 1955 women on their first or second day postpartum. The interview was based on a questionnaire containing 19 questions covering participants' awareness and experience of using EC as well as their future approach to its use. Results: The rate of unplanned pregnancy was 18.2% and the rate of EC awareness was 26.0%; 89.4% of those who were aware of EC knew how to use it correctly. In the multivariate regression analysis, employment, household income and level of education were independently associated with EC awareness; gravidity, household income, level of education and number of abortions were independently associated with unplanned pregnancy. Awareness of EC increased significantly ( p  < .05) with age, household income and educational level; knowledge about the correct use of EC increased with age and educational level ( p  < .05). Conclusion: EC awareness among the study population was low and was related to household income and educational level. Household income, educational level and gravidity were the most important factors associated with unplanned pregnancy. Governments must therefore establish appropriate health policies and provide contraceptive education to women from adolescence onwards.